Winning Strategies for Successful Aging - Eric Pfeiffer (Yale University Press, 2013)
Winning Strategies for Successful Aging is based on my experience as a psychiatrist and a gerontologist. For some 12 years I was a member of the Duke University Center for the Study of Aging in Durham, North Carolina, and for more than 30 years I served as the Founding Director of the Suncoast Alzheimer’s and Gerontology Center at the College of Medicine at the University of South Florida in Tampa. In these positions I had the opportunity to treat and to study thousands of older people and their loved ones as they navigated this critical phase of their lives. I learned from them and from my research what works and what doesn’t work. This is my attempt to distill that knowledge and make it available to you. I want this to be a conversation between you and me that is useful, practical, and understandable, so that you can make this phase of your life enjoyable, successful, and relatively trouble-free.